The Relationship between Sociodemographic and Obstetric Characteristics and Adherence to Iron Supplementation among Pregnant Women - Susilawati Susilawati; Ranti Lestari; Nuur Octascriptiriani; Shinta Utami; Naura Khaira Zahra Hasnul Aziz (Borneo Scientific Publishing, 2026)
The high prevalence of anemia among pregnant women remains a serious public health problem. Adherence to iron supplementation is one strategy to prevent and control anemia during pregnancy. This study aimed to determine the relationship between sociodemographic and obstetric characteristics and adherence to iron supplementation among pregnant women. A cross-sectional study was conducted among 72 pregnant women using total sampling in Cisarua Village, within the service area of Puskesmas Sukabumi, Sukabumi City. Data were collected using validated instruments, including a demographic questionnaire and the Morisky Medication Adherence Scale (MMAS-8). Data were analyzed using chi-square tests and logistic regression. The results showed significant associations between maternal age, education level, employment status, gestational age, parity, diagnosis of anemia, economic status, and information sources and adherence to iron supplementation (p < 0.05). Multivariate analysis identified employment status as the strongest predictor of adherence (OR = 445.043), indicating that employed pregnant women were more likely to adhere to iron supplementation than unemployed pregnant women. These findings suggest that sociodemographic and obstetric characteristics are significantly associated with adherence to iron supplementation among pregnant women.